Monounsaturated Fatty Acid Levels May Not Affect Cardiovascular Events: Results From a Mendelian Randomization Analysis - Mazidi, Mohsen; Katsiki, Niki; Shekoohi, Niloofar; Banach, Maciej (Frontiers in Nutrition, 2020)
Background/Aim: Several observational studies evaluated the links between serum monounsaturated fatty acids (MUFAs) and cardiovascular events with controversial results. In the present study, Mendelian Randomization (MR) analysis was applied to obtain unconfounded estimates of the casual associations of genetically determined serum MUFAs with coronary heart disease (CHD), myocardial infarction (MI), cardioembolic stroke (CS)and ischemic stroke (IS). Methods: Four MUFAs were studied (i.e. 10-heptadecenoate, Myristoleic, Oleic and Palmitoleic acid). Data from the largest genome-wide association studies (GWAS) on MUFAs, CHD, MI and stroke were analyzed. Inverse variance weighted method (IVW), weighted median (WM)-based method, MR-Egger, as well as MR-Pleiotropy RESidual Sum and Outlier (PRESSO) were applied. To rule out the impact of single-nucleotide polymorphism (SNP), the leave-one-out method was also performed. Results: Genetically higher serum 10-heptadecenoate levels did not affect the risk of CHD (IVW=Beta: -0.304, p= 0.185), MI (IVW=Beta: -0.505, p=0.066), CS (IVW=Beta: -0.056, p=0.945) and IS (IVW=Beta: -0.121, p=0.767). Similarly, no significant associations were observed for the Myristoleic acid (CHD: IVW=Beta: 0.008; MI: IVW=Beta: 0.041; CS: IVW=Beta: 0.881; IS: IVW=Beta: 0.162), the Oleic acid (CHD: IVW=Beta: -0.2417; MI: IVW=Beta: -0.119; CS: IVW=Beta: 1.059; IS: IVW=Beta: 0.008491), and the Palmitoleic acid (CHD: IVW=Beta: -0.06957; MI: IVW=Beta: -0.01255; CS: IVW=Beta: 1.042; IS: IVW=Beta: -0.1862).A low likelihood of heterogeneity and pleiotropy was reported and the observed associations were not driven by single SNPs. Conclusions: In the present MR analysis, serum MUFAs levels were not associated with the risk of CHD, MI, CS and IS. Further research, evaluating more MUFAs, is required to elucidate the links between MUFAs and CVD, to contribute to health policy decisions in reducing CVD risk.